Intelligent virtue - Annas, Julia (Oxford : Oxford University Press, 2011)
Julia Annas offers an account of virtue and happiness as central ethical ideas. She argues that exercising a virtue involves practical reasoning of the kind we find in someone exercising an everyday practical skill. This helps us to see virtue as part of an agent's happiness.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Virtue